E-077 Carotid ultrasound findings and stenosis severity at enrollment in CREST 2. (23rd July 2022) - Heck, D; Roubin, G; Moore, W; Howard, G; Meschia, J; Brown, R; Brott, T; Lal, B
Abstract : Introduction: Prior treatment trials of asymptomatic carotid disease have not established a relationship of stenosis severity and outcomes. However, a recent population-based study reported stroke risk to be linearly associated with degree of ipsilateral stenosis, where compared to the 58% of participants with 50–99%, the 26% with 70–99% were at higher risk of stroke over 5 years (0 vs 14.6%), and the 16% who had 80–99% stenosis (18.3%). We examined baseline carotid duplex ultrasound characteristics of patients randomized into the Carotid Revascularization and Medical Management for Asymptomatic Carotid Stenosis Trial (CREST-2) to assess the degree of stenosis, pertinent to generalizability of the CREST-2 treatment comparisons. Materials and Methods: Patients were examined via a standardized duplex US protocol at credentialed US labs with images reviewed centrally. Peak systolic velocity (PSV), end diastolic velocity (EDV), and internal carotid to common carotid velocity ratios (ICA:CCA) were derived. Eligibility for randomization required a PSV ≥230cm/sec plus one of the following: EDV ≥100cm/sec, ICA:CCA ≥ 4, CTA or MRA ≥70%; or, a catheter angiogram (CBA) with ≥70% stenosis. Results: Of the first 1583 patients enrolled, 1520 patients had a PSV >=230 cm/s, and 63 patients enrolled based on CTA/MRA/CBA had a PSV <230 (distribution shown in Figure ). Of these, 701 (44%) patients had an EDV≥100, and 882 (56%) patients had an EDV<100. Of those 882 patients with a 'low' EDV, 626 (71%) patients had an ICA/CCA ratio ≥ 4.0, and 256 (29%) patients had an ICA/CCA ratio < 4. These 256 were enrolled based CTA/MRA/CBA. Of the 1583, 496 (31%) had a PSV ≥400 and 171 (11%) had a PSV ≥500. Conclusion: The CREST-2 eligibility criteria were specified to recruit individuals with a high degree of stenosis. However, even within this group of patients with a (likely) high degree of stenosis, there was a surprising heterogeneity between patients in the pattern of flows that qualified for the study, introducing the opportunity to assess differential treatment effects between those with different patterns. Disclosures: D. Heck: 2; C; Stryker. G. Roubin: 2; C; Consultant for Inspire MD Inc, Contego Medical, Cook Inc. W. Moore: None. G. Howard: None. J. Meschia: None. R. Brown: None. T. Brott: None. B. Lal: None.